Proximate Factors Underpinning Receiver Responses to Deceptive False Alarm Calls in Wild Tufted Capuchin Monkeys: Is It Counterdeception?. Issue 7 (26th November 2012) - WHEELER, BRANDON C.; HAMMERSCHMIDT, KURT; Higham, James P.; Semple, Stuart
<x xml:space="preserve">Abstract</x> Previous research demonstrates that tufted capuchin monkeys use terrestrial predator alarm calls in a functionally deceptive manner to distract conspecifics when feeding on contestable resources, although the success of this tactic is limited because listeners frequently ignore these calls when given in such situations. While this decreased response rate is suggestive of a counterstrategy to deception by receivers, the proximate factors underpinning the behavior are unclear. The current study aims to test if the decreased response rate to alarm calls in competitive contexts is better explained by the perception of subtle acoustic differences between predator‐elicited and deceptive false alarms, or by receivers varying their responses based on the context in which the signal is received. This was tested by first examining the acoustic structure of predator‐elicited and deceptive false alarms for any potentially perceptible acoustic differences, and second by comparing the responses of capuchins to playbacks of each of predator‐elicited and false alarms, played back in noncompetitive contexts. The results indicate that deceptive false alarms and predator‐elicited alarms show, at best, minimal acoustic differences based on the structural features measured. Likewise, playbacks of deceptive false alarms elicited antipredator reactions at the same rate as did predator‐elicited alarms, although there was a nonsignificant tendency for false alarms to be more likely to elicit escape reactions. The lack of robust acoustic differences together with the high response rate to false alarms in noncompetitive contexts suggests that the context in which the signal is received best explains receiver responses. It remains unclear, however, if listeners ascribe different meanings to the calls based on context, or if they generally ignore all signals in competitive contexts. Whether or not the decreased response rate of receivers directly stems from the deceptive use of the calls cannot be determined until these latter possibilities are rigorously tested. Am. J. Primatol. 75:715‐725, 2013. © 2012 Wiley Periodicals, Inc.